Medical record abstraction in a hospital with paper-based records: experience of early career psychiatrists in northern Borneo - Farah Ahmad Shahabuddin; Kheng, Yee Wah; Ryna Imma Buji; Nurul Syeema Zulkafli; Shea, Wah Lee; Hui, Lee Soon; Siau, Yun Yap; Vuii, Law; Loo, Jiann Lin (Cambridge University Press, 2020)
We used medical record abstraction to conduct research in a psychiatric hospital with paper-based medical records. The challenges we encountered included: the difficulty in retrieving files; the extensive effort and time needed to extract clinical information; the lack of a standardised documentation system of medical records; and the need for advanced computer literacy. To promote future research using electronic medical records, potential solutions include creating a registry of all patients receiving treatment, as well as equipping busy clinicians with computer skills.